Pengembangan Usaha Rumahan Melalui Perhitungan Harga Pokok Produksi, Penerapan K3, dan Pemasaran Digital - Widiastuti Widiastuti; Zulfa Zakiatul Hidayah; Suhendra Suhendra; Hafsari Prabhamanik Faddila; Dwi Auli Ramadhania (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
"GarasiMenul", a home-based traditional cake business located in Hegarmukti Village, Central Cikarang, Bekasi Regency, holds strategic market potential but faces operational management constraints. The partner's primary issues include inaccurate Cost of Goods Sold (COGS) calculations that exclude overhead and depreciation costs, the lack of Occupational Health and Safety (/K3) standards and Standard Operating Procedures (SOPs) in the kitchen area, and reliance on conventional marketing. This Community Service (PKM) initiative aims to optimize COGS calculation for financial accuracy, implement K3 standards and production SOPs, and apply digital marketing strategies to expand market reach. The offline implementation methodology comprised five stages: program socialization, training (financial literacy, K3, and product photography/copywriting), technology implementation (COGS spreadsheet, K3 equipment, SOP modules, and registration on GrabFood/GoFood and Google Maps), intensive mentoring and evaluation for one month, and program sustainability through printed user modules. The results demonstrated a significant enhancement in partner capacity. The partner successfully transitioned to digital spreadsheet-based bookkeeping, implemented kitchen SOPs and safety protocols, and actively leveraged digital media and online food delivery platforms. Overall, the program improved operational efficiency, financial governance accuracy, workplace safety, and market reach expansion in the digital era.